Monensin occurrence in surface water and its impact on aquatic biota in a stream of the southeast Pampas, Argentina - Pérez, Débora Jesabel; Okada, Elena; Iturburu, Fernando; De Geronimo, Eduardo; Canton, German Jose; Aparicio, Virginia Carolina; Costa, Jose Luis; Menone, Mirta Luján (Springer Science, 2020)
Monensin is an ionophore antibiotic used as a feed additive and growth promoter in cattle production worldwide. The occurrence of monensin in aquatic surficial ecosystems is of concern due to its possible detrimental effects on human health and native biota. Argentina is one of the most important cattle beef producers worldwide; however, there is little knowledge on the environmental occurrence of monensin and the associated risks to aquatic biota. In this study, we developed a method for the extraction and quantification of monensin in surface water; then, we evaluated the occurrence of monensin in a stream impacted by different animal husbandry’s operations, and then, we analyzed the ecological implications of monensin residues on aquatic organisms using the risk quotient (RQ) method. Sampling was carried out on August 2017 from the headwaters to the floodplain of the El Pantanoso stream, Buenos Aires province, Argentina. Monensin detection frequency was 75% (n = 20). The median level was 0.40 μg/L and the maximum concentration was 4.70 μg/L. The main input of monensin was from a cattle slaughterhouse, an activity that has not been considered before in the literature as a source of emission of veterinary pharmaceuticals into the environment. The RQ assessment showed that monensin levels could have potential negative effects on aquatic biota in the sampling site closest to the cattle slaughterhouse. The data obtained in this study shows that monensin was present in El Pantanoso surface waters at levels of high ecotoxicological risk to aquatic biota.